Evaluation of stress, serum, and salivary ghrelin and cortisol levels in smokers and non‐smokers with Stage III periodontitis: A cross‐sectional study. Issue 8 (25th January 2022) - Rahate, Priyanka S.; Kolte, Rajashri A.; Kolte, Abhay P.; Lathiya, Vrushali N.; Gupta, Madhur; Chari, Suresh
Abstract: Background: The present study aimed to investigate the serum and salivary ghrelin and cortisol levels in smokers and non‐smokers with Stage III Periodontitis. Methods: The present study comprised of a total of 90 systemically healthy patients categorized in three groups: Group I‐ Periodontally healthy patients; Group II‐Non‐smokers with Stage III Periodontitis and Group III‐Smokers with Stage III periodontitis. Clinical parameters of Probing pocket depth (PPD), Clinical attachment levels (CAL), Plaque Index (PI), Gingival Index (GI) and Papillary Bleeding Index (PBI) were recorded and biochemical parameters of serum and salivary ghrelin and cortisol levels were analyzed via Enzyme Linked Immunosorbent Assay (ELISA). Stress levels were assessed using Zung's self‐rating depression scale. Results: Serum and salivary ghrelin values were found to be higher in Group II (620.25 ± 260.86 pg/mL, 892.40 ± 271.65 pg/mL respectively) as compared to Group III. Similarly, salivary as well as serum cortisol levels were higher in Group III (20.78 ± 9.23 pg/mL, 399.37 ±189.21 pg/mL respectively) as compared to Group II (16.36 ± 8.88 pg/mL, 320.68 ± 107.01 pg/mL respectively). In Group III, a direct correlation was observed between stress, serum and salivary cortisol levels while an inverse correlation was found between stress, serum and salivary ghrelin levels. Group III showed a greater number of depressed patients followed by Group II and I. Conclusion: As per the results smokers with Stage III Periodontitis exhibit an elevated stress and cortisol levels, lower serum and salivary ghrelin levels as compared to the non‐smokers.